2020
DOI: 10.3390/ijms21155524
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Mesenchymal Stem Cell-Based Therapy in Mouse Models of Vascular Cognitive Impairment

Abstract: Closely linked to Alzheimer’s disease (AD), the pathological spectrum of vascular cognitive impairment (VCI) is known to be wide and complex. Considering that multiple instead of a single targeting approach is considered a treatment option for such complicated diseases, the multifaceted aspects of mesenchymal stem cells (MSCs) make them a suitable candidate to tackle the heterogeneity of VCI. MSCs were delivered via the intracerebroventricular (ICV) route in mice that were subjected to VCI by carotid artery st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Ischemia-induced neuron damage as well as dendritic and synaptic abnormalities can lead to neuronal dysfunction, which is the primary cause of cognitive impairment in VD [1]. MSCs are known as "sentinel and safe-guards of injury" and promote neuroprotection in various neurological diseases, including AD, ischemic stroke (IS), and vascular cognitive impairment (VCI) [28]. It was found that the neuroprotective effects of MSC depended primarily on exosome-mediated paracrine rather than cell replacement [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-induced neuron damage as well as dendritic and synaptic abnormalities can lead to neuronal dysfunction, which is the primary cause of cognitive impairment in VD [1]. MSCs are known as "sentinel and safe-guards of injury" and promote neuroprotection in various neurological diseases, including AD, ischemic stroke (IS), and vascular cognitive impairment (VCI) [28]. It was found that the neuroprotective effects of MSC depended primarily on exosome-mediated paracrine rather than cell replacement [29].…”
Section: Discussionmentioning
confidence: 99%
“…Human mesenchymal stem cells (hMSCs) were prepared as described previously 14 , 24 . Human MSCs were expanded in media containing minimal essential alpha 1x medium (MEMα1x; Gibco, Waltham, MA, USA), 10% fetal bovine serum (FBS; Biowest, Riverside, MO, USA), and 0.5% gentamicin (Gibco, Waltham, MA, USA) at 37°C in a 5% CO2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The expressions of immune and inflammatory markers and engraftment of hMSCs were evaluated by performing immunohistochemical (IHC) staining. IHC was carried out by referring to studies reported previously 14 , 24 . On Day 7, mice that were randomly allocated to undergo IHC analysis was sacrificed via cardiac perfusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemia-induced neuron damage as well as dendritic and synaptic abnormalities can lead to neuronal dysfunction, which is the primary cause of cognitive impairment in VD [1]. MSCs are known as "sentinel and safe-guards of injury" and promote neuroprotection in various neurological diseases, including AD, ischemic stroke (IS), and vascular cognitive impairment (VCI) [21]. It was found that the neuroprotective effects of MSC depended primarily on exosome-mediated paracrine rather than cell replacement [22].…”
Section: Discussionmentioning
confidence: 99%